Diversity and distribution of Oxytropis DC. (Fabaceae) species in Asian Russia - Sandanov, Denis V.; Dugarova, Anastasiia S.; Brianskaia, Elena P.; Selyutina, Inessa Yu; Makunina, Natalia I.; Dudov, Sergey V.; Chepinoga, Victor V.; Wang, Zhiheng (Biodiversity data journal, 2022)
BACKGROUND: The dataset providing information on the geographic distribution of Oxytropis species on the territory of Asian Russia is discussed. The data were extracted from different sources including prominent floras and check-lists, Red Data books, published research on congeneric species and authors' field observations and mainly cover less-studied, remote regions of Russia. The dataset should be of value to applied, basic and theoretical plant biologists and ecologists interested in the Oxytropis species. NEW INFORMATION: The dataset includes 5172 distribution records for 143 species and 15 subspecies of genus Oxytropis DC. (Fabaceae Lindl.) in Asian Russia. The dataset fills gaps in the distribution of locoweeds in the study area and contains precise coordinates for many of rare and endemic species.
Keywords: dataset; digitised printed maps; diversity patterns; field observations; occurrences